Comparative Performance Evaluation of Routine Malaria Diagnosis at Ho Municipal Hospital - James Osei-Yeboah; Gameli Kwame Norgbe; Sylvester Yao Lokpo; Mohammed Khadijah Kinansua; Loverage Nettey; Emmanuel Alote Allotey (Journal of Parasitology Research)
Differences in quality performance score had been reported for the routinely used diagnostic methods for malaria at different settings. There is therefore a need to evaluate the test performance of the routine diagnostic methods for malaria detection in Ho, a setting with no recorded quality evaluation on malaria diagnosis. The hospital-based cross-sectional study was conducted comprising 299 outpatients. Patients were first seen and presumptively diagnosed with malaria by a clinician and were referred to the laboratory for confirmation (microscopy and Rapid Diagnostic Test). The performance analysis included sensitivity, specificity, receiver operating characteristics (ROC), weighted kappa, Youden index, and p value. Out of the 299 patients, 221 patients were positive by presumptive diagnosis, 35 were positive by Rapid Diagnostic Test (RDT), and 25 were positive by microscopy. Using microscopy as the gold standard, RDT had sensitivity of 62.5% and specificity of 92.73%, whilst presumptive diagnosis had a sensitivity of 70.83% and specificity of 25.82%. The RDT recorded ROC of 0.697 with p value of 0.0001. The presumptive diagnosis recorded ROC of 0.506 with p value of 0.7304. Though none of the test methods evaluated over the gold standard achieved the WHO recommended diagnostic sensitivity and specificity, the RDT achieved an acceptable agreement with the gold standard.